2010
DOI: 10.1159/000306448
|View full text |Cite
|
Sign up to set email alerts
|

De novo Renal Transplantation after Kaposi Sarcoma: Favorable Outcome in a Patient Receiving Sirolimus and Mycophenolate-Based Immunosuppression

Abstract: Immunosuppressive treatment increases the risk of infection and malignancy in organ transplant recipients. We report on a 42-year-old male renal transplant recipient who lost his first graft after reduction of immunosuppressive treatment due to Kaposi sarcoma and who successfully underwent a second renal transplant 10 years later. The patient’s current treatment consists of low-dose prednisone, and the two antiproliferative immunosuppressants mycophenolate mofetil and rapamycin. 4.5 years after his second tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Sirolimus (rapamycin), an immunosuppressive drug used in kidney-transplant recipients, probably has antineoplastic effects. The immunosuppressive and antineoplastic effects of sirolimus may be due to a common mechanism [98][99][100][101]. It is thought that sirolimus inhibits not only production of VEGF but also dampens its effects on endothelial cells, and it has been suggested that sirolimus inhibits the progression of Kaposi's sarcoma in kidney-transplant recipients while exerting an antirejection effect on organ allografts [98].…”
Section: Human Herpesvirus 6 Human Herpesvirus 7 and Human Herpesvimentioning
confidence: 99%
“…Sirolimus (rapamycin), an immunosuppressive drug used in kidney-transplant recipients, probably has antineoplastic effects. The immunosuppressive and antineoplastic effects of sirolimus may be due to a common mechanism [98][99][100][101]. It is thought that sirolimus inhibits not only production of VEGF but also dampens its effects on endothelial cells, and it has been suggested that sirolimus inhibits the progression of Kaposi's sarcoma in kidney-transplant recipients while exerting an antirejection effect on organ allografts [98].…”
Section: Human Herpesvirus 6 Human Herpesvirus 7 and Human Herpesvimentioning
confidence: 99%
“…Il n'y a aucun élément qui permet d'affirmer que le taux de SKPT est plus élevé avec tel ou tel immunosuppresseur. À l'inverse la prescription de la rapamycine (ou sirolimus) semble présenter un intérêt car plusieurs auteurs ont rapporté des cas d'amélioration ou de régres-sion du SKPT après le remplacement de la ciclosporine ou du tacrolimus par le sirolimus [15,16,17]. Le sirolimus posséde à la fois des propriétés immunosuppressives, anti-tumorales et anti-angiogéniques : c'est donc une drogue particulièrement intéressante chez les patients ayant un risque de SKPT.…”
Section: éTiopathogénie Et Facteurs De Risqueunclassified
“…Si ces patients sont re-transplantés, ils ont un risque non négligeable, mais non quantifiable, de développer un nouveau SKPT, et donc de perdre le deuxième greffon et de retourner en dialyse [41]. Cependant, dans plusieurs cas où il n'y a pas eu de récidive du SKPT après la 2 e greffe [15,42]. Dans le cas rapporté, l'association chirurgie / modification du traitement immunosuppresseur a permis d'obtenir une évo-lution favorable.…”
Section: éVolutionunclassified